The The Self-Concept and Feelings of Guilt and Shame in Patients with Psoriatic Arthritis: A Literature Review - Polenko, Vasiliy V. (Futurity Medicine, 2026)
Background: Psoriatic arthritis (PsA) is a chronic, systemic autoimmune disease that severely compromises patients' physical and psychosocial well-being. This literature review aims to synthesise contemporary scientific data to examine the multi-layered self-concept in PsA patients and evaluate the bidirectional, stress-mediated relationships between psychological attributes and somatic disease progression from a psychotherapeutic perspective. Methods: A systematic literature search was conducted across international and national electronic databases (PubMed, ScienceDirect, ResearchGate, eLibrary, CyberLeninka) and finalized in January 2026. The search targeted peer-reviewed clinical, observational, qualitative studies, and meta-analyses published between 2015 and 2025, focusing on psychosomatic manifestations, illness representations, and emotional constructs in PsA. Results: The findings demonstrate that the self-concept in PsA patients operates across three hierarchical levels: somatic, evaluative, and cognitive-behavioural. At the somatic level, visible skin lesions and chronic pain catalyze body dissatisfaction and skin-related shame. At the evaluative level, shame and unconscious racket guilt, examined through transactional analysis, operate as destructive internalized auto-aggression. Recent neuroimmune data confirm that depression in PsA serves as a true somatic comorbidity driven by the CRH-MC-Th17 axis. At the cognitive-behavioural level, patients exhibit severe cognitive uncertainty across Leventhal’s Common-Sense Model, while alexithymia acts as a key predictor of disease exacerbation. Conclusion: The review concludes that the psychological burden of PsA is intricately linked to its pathogenetic mechanisms, with unconscious racket guilt and alexithymia representing key predictors of disease exacerbation. Consequently, there is an urgent need to validate specific psychometric tools for guilt in PsA and to integrate specialised psychotherapy alongside psychopharmacotherapy into standard clinical guidelines to improve remission quality and reduce the healthcare system burden.